El pensamiento sociológico aún vigente, el expertise en la actualidad - Mejía, Alessandro Nicolas (2023)
The book Pensando Sociológicamente by Zygmunt Bauman and Tim May has become a classic work in the contemporary sociological discipline and, why not say it, in the social sciences. In this writing, the author proposes the approach to sociology as an instrument that provides us with the ability to study social relationships, analyzing experiences together with others and understanding them as part of a network of personal interrelationships, in addition to addressing the marked difference between everyday common sense and the sociological discipline. Finally, the social relevance of the book is highlighted, since it mentions the concept of technological expertise, from which it is feasible to extract an example and link it to the new form of remote work originated from social isolation due to covid-19.